Relasi Kekuasaan dalam Pernikahan Anak dan Implikasinya terhadap Kesejahteraan Anak: Perspektif Filsafat Hukum Islam - Nisanur Khotimah (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2025)
Child marriage remains a persistent social and legal challenge in Indonesia despite the enactment of Law Number 16 of 2019, which raised the minimum legal age for marriage. This study examines child marriage from the perspectives of positive law, Islamic law, power relations theory, and maqāṣid al-syarī‘ah, while exploring its implications for child welfare. A qualitative library research approach was employed through the analysis of legislation, classical and contemporary Islamic legal literature, scholarly articles, and relevant previous studies. The findings reveal that child marriage is influenced not only by economic conditions, educational attainment, social environments, and religious interpretations but also by unequal power relations operating within families, communities, and social institutions. The authority exercised by parents, religious leaders, and prevailing cultural norms often constrains children's autonomy in deciding whether and when to marry. From the perspective of maqāṣid al-syarī‘ah, child marriage has the potential to undermine the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). This study argues for the reconstruction of Islamic family law based on maṣlaḥah, child protection, and equitable family relationships in order to prevent structural domination and promote children's welfare, dignity, and fundamental rights.